THE INFLUENCE OF WAGE COMPENSATION AND AWARDS TO WORK SPIRIT - Feriyana, Winda (Fakultas Ekonomi Universitas IBA, 2020)
This study aims to analyze partially or jointly about the effect of wage compensation, appreciation of employee morale and analyze the most dominant variables in influencing employee morale in the Manufacture of Roof Tile and Bricks in Belitang, East OKU. With a correlation coefficient of 0.935 at the 95% confidence level, it was obtained an understanding that wage and award compensation simultaneously had a positive influence on work morale of 86.5% and had a significant influence. This is confirmed by the analysis of the coefficient of determination (Adjusted Rsquare) the effect of wage compensation and appreciation for employee work spirit in Belitang, East OKU Manufacture of Roof Tile and Bricks at 0.865. This research was conducted to 30 respondents with the analytical method used is path analysis using SPSS software.